2016
DOI: 10.1044/2015_ajslp-14-0137
|View full text |Cite
|
Sign up to set email alerts
|

Early Language Intervention Using Distance Video-Teleconferencing: A Pilot Study of Young Boys With Fragile X Syndrome and Their Mothers

Abstract: No previous study has examined a distance-delivered parent-implemented language intervention for young boys with fragile X syndrome. Mothers were able to increase their use of verbally responsive language. Intervention efficacy might be enhanced by incorporating an augmentative and alternative communication device for some children and a more concerted focus on increasing the frequency of child communication acts. Findings provide preliminary support for the efficacy of the distance delivery format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 86 publications
(106 reference statements)
1
37
0
Order By: Relevance
“…Results of this double-blind placebo-controlled study should be available in 2017; however, open-label results of a FXS Cogmed feasibility study involving 17 males and females, mean age 12.49 years, were reported by Au and colleagues [94]. Learning paradigms focused on language have recently been shown to have efficacy for individuals with FXS over a wide age range (e.g., [95, 96]) and, like Cogmed, could be useful as outcome measures, with the added benefit of “boosting” the effects of pharmacological treatments.Novel adaptive behavior measures.Independent Living Scales (ILS; [97]). The ILS is a measure of adaptive behavior that assesses the ability to function independently and handle real-life situation.…”
Section: Cognitive Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of this double-blind placebo-controlled study should be available in 2017; however, open-label results of a FXS Cogmed feasibility study involving 17 males and females, mean age 12.49 years, were reported by Au and colleagues [94]. Learning paradigms focused on language have recently been shown to have efficacy for individuals with FXS over a wide age range (e.g., [95, 96]) and, like Cogmed, could be useful as outcome measures, with the added benefit of “boosting” the effects of pharmacological treatments.Novel adaptive behavior measures.Independent Living Scales (ILS; [97]). The ILS is a measure of adaptive behavior that assesses the ability to function independently and handle real-life situation.…”
Section: Cognitive Measuresmentioning
confidence: 99%
“…Learning paradigms focused on language have recently been shown to have efficacy for individuals with FXS over a wide age range (e.g., [95, 96]) and, like Cogmed, could be useful as outcome measures, with the added benefit of “boosting” the effects of pharmacological treatments.…”
Section: Cognitive Measuresmentioning
confidence: 99%
“…follow child's lead, appropriate use of prompts, focus on child's object of interest, and linguistically map accordingly). Initial results for children with Fragile X syndrome suggest the feasibility and potential effectiveness of this approach (McDuffie et al 2015). As this strategy develops and is further refined, greater opportunities for establishing a true discourse framework will exist, allowing continuity of this and related relationship processes to emerge over time.…”
Section: Sensitive Responsiveness and Relationshipsmentioning
confidence: 99%
“…A number of narrative reviews have concluded that therapy for childhood speech and language impairment via telepractice is feasible and valid (149,151,152,(159)(160)(161). However, there are no published systematic reviews describing the use of telepractice for paediatric speech and language screening.…”
Section: Efficacy and Adoption Of Speech Pathology Telepracticementioning
confidence: 99%
“…These studies report that SLPs are often reluctant to provide direct services due to concerns regarding the efficacy of assessment and therapy interventions delivered via telepractice. It is interesting that this perception continues despite a growing evidence base in the area of speech pathology telepractice (32,(147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159)(160)(161).…”
Section: Suitability Of Patient Groups and Services For Telepracticementioning
confidence: 99%